1986
DOI: 10.1016/0304-405x(86)90070-x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting returns in the stock and bond markets

Abstract: Several predetermined variables that reflect levels of bond and stock prices appear to predict returns on common stocks of firms of various sizes, long-term bonds of various default risks, and default-free bonds of various maturities. The returns on small-firm stocks and low-grade bonds are more highly correlated in January than in the rest of the year with previous levels of asset prices, especially prices of small-firm stocks. Seasonality is found in several conditional risk measures, but such seasonality is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
750
1
6

Year Published

1994
1994
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,556 publications
(794 citation statements)
references
References 38 publications
37
750
1
6
Order By: Relevance
“…This line of research has quite some history for equity premium prediction and has developed established indicators, such as the short-term interest rate, the credit and the term spread (see, e.g., Ang & Bekaert, 2007;Fama & French, 1989; Keim & Stambaugh, 1986), the inflation rate (e.g., Campbell & Vuolteenaho, 2004;Fama & Schwert, 1977;Nelson, 1976), stock market volatility (investigated by Guo, 2006), or the consumption-wealth ratio provided by Lettau and Ludvigson (2001), to name just a few. Most of the empirical studies (e.g., Campbell & Shiller, 1988;Cochrane, 2008;Lewellen, 2004) use valuation ratios such as the dividend yield, the price-earnings ratio, or the book-to-market ratio, which should serve as proxies for expected business conditions, as mentioned by Campbell and Diebold (2009).…”
Section: Introductionmentioning
confidence: 99%
“…This line of research has quite some history for equity premium prediction and has developed established indicators, such as the short-term interest rate, the credit and the term spread (see, e.g., Ang & Bekaert, 2007;Fama & French, 1989; Keim & Stambaugh, 1986), the inflation rate (e.g., Campbell & Vuolteenaho, 2004;Fama & Schwert, 1977;Nelson, 1976), stock market volatility (investigated by Guo, 2006), or the consumption-wealth ratio provided by Lettau and Ludvigson (2001), to name just a few. Most of the empirical studies (e.g., Campbell & Shiller, 1988;Cochrane, 2008;Lewellen, 2004) use valuation ratios such as the dividend yield, the price-earnings ratio, or the book-to-market ratio, which should serve as proxies for expected business conditions, as mentioned by Campbell and Diebold (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the decline in stock prices or the probability of a decline in stock prices through an increase in volatility causes an increase in leverage and the firm's default risk, which in turn leads to an increase in the spreads and a decline in the debt's price. The negative relationship between stock returns and credit spreads has been validated by many empirical studies: Ramaswami (1991), Shan (1994) and Kwan (1996) at the level of the individual firm; Keim and Stambaugh (1986), Campbell and Ammer (1993) at the aggregate level; and Blume et al (1991) and Cornell and Gren (1991) at the portfolio level. Campbell and Taksler (2003) found a significant positive relationship between asset volatility and credit spreads.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 86%
“…The seminal studies of Keim and Stambaugh (1986), Fama and French (1988) and Campbell and Shiller (1988) empirically demonstrated that variables such as dividend yield, book-to-market ratio, or interest rate spreads have significant predictive ability over future stock returns. Fama (1991) interpreted these findings as evidence of time-varying risk premia rather than as evidence against market efficiency.…”
Section: Introductionmentioning
confidence: 99%